2015
DOI: 10.1259/bjr.20140372
|View full text |Cite
|
Sign up to set email alerts
|

4D radiobiological modelling of the interplay effect in conventionally and hypofractionated lung tumour IMRT

Abstract: Objective: To study the impact of the interplay between respiration-induced tumour motion and multileaf collimator leaf movements in intensity-modulated radiotherapy (IMRT) as a function of number of fractions, dose rate on population mean tumour control probability (TCP pop ) using an in-house developed dose model. Methods: Delivered dose was accumulated in a voxel-byvoxel basis inclusive of tumour motion over the course of treatment. The effect of interplay on dose and TCP pop was studied for conventionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…PBS-PT has therefore mainly been offered to patients with limited breathing motion [14]. However, recent studies with PBS-PT confirm that interplay uncertainties are canceled out by fractionation-as for IMRT-and more attention should be focused on changes in breathing patterns and anatomy [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…PBS-PT has therefore mainly been offered to patients with limited breathing motion [14]. However, recent studies with PBS-PT confirm that interplay uncertainties are canceled out by fractionation-as for IMRT-and more attention should be focused on changes in breathing patterns and anatomy [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, these data were acquired after only one fraction of treatment, under which interplay effects can have a more significant effect (and arguably are more relevant within a hypofractionated SBRT context). 8,[25][26][27][28][29] Since our irregular breathing traces were "re-played" for both imaging and treatment, our study arguably only addresses the first category of characteristic irregularity identified by Mutaf et al 13 Moreover, in our phantom we verified dose at the tumor center, so cannot fully address the issue of target coverage and peripheral dose. To the first point, baseline drifts were seen in some of our breathing traces; so when coupled with the random time points chosen for both imaging and treatment, together with the delivery of multiple fractions, this at least supports the notion that some systematic errors were propagated through to treatment delivery.…”
Section: Discussionmentioning
confidence: 95%
“…As at scanning, no specific section of the breathing trace was targeted for "beam on", and three fractions of each treatment plan were delivered to mitigate against any interplay effects that may confound a single measurement. 8,[25][26][27][28][29] Therefore in total over 100 treatment deliveries were completed, not including calibration fields. To this end, treatment was delivered effectively randomly over multiple portions of each breathing trace.…”
Section: Dosimetrymentioning
confidence: 99%
“…Although, the main purpose of TCP/NTCP calculations has been to provide a surrogate tool for plan comparisons and optimum plan selection for a given treatment, there are many other investigations that have employed this approach to quantize the radiobiological consequences for different available modalities, and geometric errors, as well as comparing novel techniques for radiation therapy [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Moreover, several studies have utilized radiobiological modeling to evaluate the effect of geometric errors in image guided radiation therapy (IGRT), while others have applied this modeling for brachytherapy planning as well as radiation therapy with heavy ion beams [25][26][27][28][29][30][31][32].This article intends to review briefly the recent studies on application of radiobiological modeling in current radiation therapy practice. Additionally, it is an attempt to gather the information on the application of radiobiological modeling in various areas of research in clinical practice and to represent the potential of current biological modeling in radiation therapy.…”
mentioning
confidence: 99%